STRATEGI ADAPTASI SOSIAL KELUARGA MISKIN DALAM MENGHADAPI PANDEMI : ANALISIS KETAHANAN SOSIAL - Jenny Sintike; Chyntia Yolanda Sahetaphy2; Heni Josanal Kalasa; Aldy Behuku; Juan Pascal Samallo (JURNAL BADATI, 2023)
Child sexual abuse is a serious problem that requires comprehensive handling, especially in aspects of trauma recovery. This research aims to analyze social workers' micro intervention models in handling trauma of child sexual abuse victims through a systematic literature review approach. The research method involves analyzing 50 scientific articles published between 2013-2024, focusing on the implementation and impact of micro interventions. The results show that Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) is the most effective intervention model with a 75% success rate. Interventions successfully reduced PTSD symptoms by 65%, improved social functioning in 55% of cases, and increased resilience in 50% of victims. Key success factors include social worker competency (85%), family support (75%), and intervention consistency (70%). This research recommends strengthening practitioner competency, developing integrated support systems, and enhancing multiprofessional collaboration to optimize intervention impact.